Mannosides as crucial part of bioactive supports for cultivation of human epidermal keratinocytes without feeder cells - Labský, Jirí; Dvoránková, Barbora; Smetana, Karel; Holíková, Zuzana; Broz, Ludomír; Gabius, Hans-Joachim (Biomaterials, 2003)
Large-scale production of keratinocytes by cell culture is of interest for medical applications. Long-term cultivation of epidermal cells is presently possible with feeder cells, i.e. 3T3 fibroblasts with arrested mitosis, or with specially formulated culture medium. To define refinements for in vitro conditions, the analysis of the natural environment with growth-maintaining/stimulating factors can provide important clues. Cells with proliferative activity are located in the basal layer of the epidermis in close contact with a basement membrane. Employing lectin and reverse lectin histochemistry of skin, muscle fibers and feeder cells, we assumed that the interplay of mannose-binding sites of epidermal cells, detected by a labeled neoglycoprotein, with glycoligands in the feeder cell layer or basement membrane could trigger signaling with relevance for adhesion and growth regulation. Indeed, coating of polystyrene with mannose-containing neoglycoprotein mimicking a mannose-rich cell matrix enabled the cultivation of keratinocytes without feeder cells in a Ca(2+)-dependent manner in serum-containing culture medium. Following this experimental demonstration of specific binding of mannose residues as part of a neoglycoprotein controlled by testing sugar-free carrier protein and other substances, we next synthesized and tested biocompatible polymers. Attachment and proliferation of keratinocytes on the surface of these polymers compared favorably to control experiments using feeder cells. In conclusion, we suggest that these polymers are bioactive offering a perspective for keratinocyte cultivation without feeder cells.
Keywords: buňky 3T3; Mannosides; Mitosis; buněčné kultury; methakryláty; Epidermal Cells; Keratinocytes; Coculture Techniques; keratinocyty; mannosidy; lidé; Animals; Humans; zvířata; Cell Culture Techniques; myši; kokultivační techniky; mitóza; epidermální buňky; Mice; Methacrylates; 3T3 Cells